Estudo da corrosão dos aços AISI 1020, 304L, 316L e duplex SAF 2205 em planta do tratamento de efluentes em indústria de celulose e papel - Gogola, Eliane Engel (2014)
In this work were studied of the chemical product’s influence once used through the membrane’s cleaning process of the ultrafiltration plant in the effluent treatment station, in a pulp and paper company, located in Paraná State – Brazil on the corrosive process presented in the plant. It was determined the electrochemical parameters through electrochemical methods, according to the norm ASTM G 59-97. It was used for the determinations a potentiostat/galvanostat AUTOLAB, model PGSTAT 30. As the electrolyte, it was used the effluent itself to be treated in the plant, and solutions of NaOH 500 mg/L, H2SO4 0,012 mol/L and 0,1 mol/L and H2O2 5,0g/L and 10,0g/L at 25ºC. The corrosion rates highest were in sulfuric acid, being that for concentration of 0,012 mol/L, was 1,26 mm/year for the steel AISI 1020, 0,54 mm/year for the AISI 304L, 0,00229 mm/year for the SAF 2205. For the steel AISI 316L there was variation between the rates measured for the electrodes removed from regions of the base metal, of the heat effected zone and of the cast zone, being 0,0055, 0,0033 and 0,0038 mm/year, respectively. For the solution of acid at 0,1 mol/L was increased the corrosion rates to all those studied metals, being more pronounced this increase to the AISI 304L, going to 0,94mm/year. Now to the duplex steel SAF 2205 the increase was lower than 5%. The effluent has a high corrosion only for steel AISI 1020, of 0,18mm/year, with lesser rates 0,004 mm/year. In this mean, the material that have had better performance was AISI 304L with values of 0,0016 mm/year. In the sodium hydroxide solution all metals had corrosion rates similar, being the least to the AISI 304L, of 0,0012 mm/year, and at most to cast zone of AISI 316L, with 0,0018 mm/year. The variation in the concentration of the solutions of hydrogen peroxide from 5,0 g/L to 10,0 g/L had no significant effect in the corrosion rates for steels AISI 316L e SAF 2205. For the steel AISI 304L the corrosion rate doubles, going from 0,014 mm/year to 0,032 mm/year, to twice the concentration. For the steel AISI 1020 was observed the opposite effect, the corrosion rate dropped almost in half, going from 0,072 mm/year to 0,037 mm/year, to increase the concentration, being intermediates between as rates observed for acid mean, more aggressive, and for alkaline mean, less aggressive. As a results of this study, it’s been possible to suggest doing a sequence to cleaning plant with objective to minimize the corrosion through the passivation of metals in alkaline mean.